2022
DOI: 10.1097/crd.0000000000000431
|View full text |Cite
|
Sign up to set email alerts
|

Vericiguat: A Novel Soluble Guanylate Cyclase Stimulator for Use in Patients With Heart Failure

Abstract: Heart failure (HF) affects 6.2 million Americans and is increasing annually in its frequency. Treatment of HF has been at the forefront of medical advancements due to the financial burden on our health care system. As such, changes to the guidelines regarding standard of care have been evolving over the last decade with the recent additions of sacubitril-valsartan and sodium glucose co-transporter-2 inhibitors to standard of care in the treatment of HF. Despite the aforementioned expansions in treatment option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In addition, some studies also recommended taking vericiguat in HF. 25,26 Finally, due to the study design, studies reporting the effects of combinations of drugs in patients with HF were not included in the present meta-analysis. Notably however, recent studies of the combination of vericiguat with isosorbide mononitrate (VISOR study) and nitroglycerin (VENICE study) showed that vericiguat slightly lowered blood pressure, similar to the placebo group, indicating minimal adverse effects of vericiguat in HF.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies also recommended taking vericiguat in HF. 25,26 Finally, due to the study design, studies reporting the effects of combinations of drugs in patients with HF were not included in the present meta-analysis. Notably however, recent studies of the combination of vericiguat with isosorbide mononitrate (VISOR study) and nitroglycerin (VENICE study) showed that vericiguat slightly lowered blood pressure, similar to the placebo group, indicating minimal adverse effects of vericiguat in HF.…”
Section: Discussionmentioning
confidence: 99%
“…It stimulates sGC directly in a NO-independent manner [ 62 ]. Vericiguat, which has similar activity, but a longer duration of action compared with riociguat, improved HF symptoms in patients and reduced death due to CV defects, with additive effects in patients receiving standard treatment for chronic HF [ 63 ].…”
Section: New Drugs For the Treatment Of Hfmentioning
confidence: 99%
“…The progression of chronic HF is inhibited when blood vessels dilate and BP is reduced. However, sGC stimulants are also effective at correcting reductions in BP, indicating that their direct action on the heart is also protective against HF [ 62 , 63 , 64 ]. In other words, a decrease in NO production by endothelial cells results in a decrease in tissue cGMP levels.…”
Section: New Drugs For the Treatment Of Hfmentioning
confidence: 99%
See 2 more Smart Citations